Association between body composition and the risk of mortality in the obese population in the United States - Lee, Heeso; Chung, Hye Soo; Kim, Yoon Jung; Choi, Min Kyu; Roh, Yong Kyun; Yu, Jae Myung; Oh, Chang-Myung; Kim, Joon; Moon, Shinje (Frontiers in Endocrinology, 2023)
Background: Recent studies have presented the concept of the obesity paradox, which suggests that individuals with obesity have a lower risk of death than those without it. This paradox may arise because BMI alone is insufficient to understand body composition accurately. This study aimed to investigate the relationship between fat and muscle mass and the mortality risk in individuals with overweight/obesity.We used data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2006 and from 2011 to 2018, which were linked to the mortality information obtained from the National Death Index. Multiple Cox regression analysis was performed to estimate the mortality risk. A subgroup analysis was conducted using propensity score matched (PSM) data for age, sex, and race/ethnicity.This study included 16,555 participants who were overweight/obesity (BMI≥25 kg/m 2 ). An increase in the appendicular skeletal muscle mass index was associated with a lower mortality risk (HR: 0.856, 95% CI: 0.802-0.915). This finding was consistent in the subgroup analysis of the PSM data. Contrastingly, a high fat mass index was associated with an increased risk of mortality. Sarcopenic overweight/obesity was significantly associated with high mortality compared to obesity without sarcopenia (HR: 1.612, 95%CI: 1.328-1.957). This elevated risk was significant in each age-and sex-based subgroup. This finding was consistent with the subgroup analysis using PSM data.In contrast to the obesity paradox, a simple increase in BMI does not protect against mortality. Instead, low body fat and high muscle mass reduce mortality risk.